A combined experimental and computational study on the transition of the calcium isopropoxide radical as a candidate for direct laser cooling. Issue 15 (30th March 2022) - Telfah, Hamzeh; Sharma, Ketan; Paul, Anam C.; Riyadh, S. M. Shah; Miller, Terry A.; Liu, Jinjun
Abstract : Vibronically resolved laser-induced fluorescence/dispersed fluorescence and cavity ring-down spectra of the electronic transition of the calcium isopropoxide [CaOCH(CH3 )2 ] radical have been obtained and simulated. Abstract : Vibronically resolved laser-induced fluorescence/dispersed fluorescence (LIF/DF) and cavity ring-down (CRD) spectra of the electronic transition of the calcium isopropoxide [CaOCH(CH3 )2 ] radical have been obtained under jet-cooled conditions. An essentially constant energy separation of 68 cm −1 has been observed for the vibrational ground levels and all fundamental vibrational levels accessed in the LIF measurement. To simulate the experimental spectra and assign the recorded vibronic bands, Franck–Condon (FC) factors and vibrational branching ratios (VBRs) are predicted from vibrational modes and their frequencies calculated using the complete-active-space self-consistent field (CASSCF) and equation-of-motion coupled-cluster singles and doubles (EOM-CCSD) methods. Combined with the calculated electronic transition energy, the computational results, especially those from the EOM-CCSD calculations, reproduced the experimental spectra with considerable accuracy. The experimental and computational results suggest that the FC matrix for the studied electronic transition is largely diagonal, but transitions from the vibrationless levels of the Ã state to the X̃-state levels of the CCC bending ( ν 14 and ν 15 ), CaO stretch ( ν 13 ), and CaOC asymmetric stretch ( ν 9 and ν 11 ) modes also have considerable intensities. Transitions to low-frequency in-plane [ ν 17 ( a ′)] and out-of-plane [ ν 30 ( a ′′)] CaOC bending modes were observed in the experimental LIF/DF spectra, the latter being FC-forbidden but induced by the pseudo-Jahn–Teller (pJT) effect. Both bending modes are coupled to the CaOC asymmetric stretch mode via the Duschinsky rotation, as demonstrated in the DF spectra obtained by pumping non-origin vibronic transitions. The pJT interaction also induces transitions to the ground-state vibrational level of the ν 10 ( a ′) mode, which has the CaOC bending character. Our combined experimental and computational results provide critical information for future direct laser cooling of the target molecule and other alkaline earth monoalkoxide radicals.